Functionalization of carboxylated lignin nanoparticles for targeted and pH-responsive delivery of anticancer drugs. (November 2017) - Figueiredo, Patrícia; Ferro, Cláudio; Kemell, Marianna; Liu, Zehua; Kiriazis, Alexandros; Lintinen, Kalle; Florindo, Helena F; Yli-Kauhaluoma, Jari; Hirvonen, Jouni; Kostiainen, Mauri A; Santos, Hélder A
Aim: To carboxylate kraft lignin toward the functionalization of carboxylated lignin nanoparticles (CLNPs) with a block copolymer made of PEG, poly(histidine) and a cell-penetrating peptide and then evaluate the chemotherapeutic potential of the innovative nanoparticles.Materials & methods: The produced nanoparticles were characterized and evaluated in vitro for stability and biocompatibility and the drug release profiles and antiproliferative effect were also assessed.Results: The prepared CLNPs showed spherical shape and good size distribution, good stability in physiological media and low cytotoxicity in all the tested cell lines. A poorly water-soluble cytotoxic agent was successfully loaded into the CLNPs, improving its release profiles in a pH-sensitive manner and showing an enhanced antiproliferative effect in the different cancer cells compared with a normal endothelial cell line.Conclusion: The resulting CLNPs are promising candidates for anticancer therapy.